Simulating streamflow variability and aquatic states in temporary streams using a coupled groundwater-surface water model. Issue 1 (2nd January 2016) - Querner, E.P.; Froebrich, J.; Gallart, F.; Cazemier, M.M.; Tzoraki, O.
Abstract: In order to apply the EU Water Framework Directive for temporary streams, it is important to quantify the space–time development of different aquatic states. We report on research on the development of aquatic states for temporary streams in the Evrotas basin, Greece. The SIMGRO regional hydrological model was used in a GIS framework to generate flow time series for the Evrotas River and all major tributaries. Five flow phases were distinguished: flood conditions, riffles, connected pools, isolated pools and dry bed conditions. Thresholds based on local hydraulic characteristics were identified per stream reach and flow phase, enabling the frequency of flow phases per month and the average frequencies for all streams to be derived. Three historical scenarios within the 20th century, marking periods of major changes in water management, were investigated. Additionally, a climate scenario for the 2050s was analysed. Simulations revealed that low flows are now much lower, mainly because more groundwater is abstracted for irrigation. The consequence is that stretches of the river fall dry during several months, causing the ecological status to deteriorate.Editor Z.W. KundzewiczAssociate editor X. Chen